Efeito da microcirculação pulpar simulada e fontes fotoativadoras na geração de calor na câmara pulpar durante restaurações bulk fill - Braga, Stella Sueli Lourenço (2017)
We evaluated the effect of light curing units (LCUs) and presence of pulpal microcirculation, on pulp chamber temperature changes used by light activation of adhesive system and bulk fill composites used to restore molar teeth. The LCUs (Bluephase G2, Ivoclar and VALO Cordless, Ultradent) were characterized regarding their irradiance and emission spectrum using MARC resin calibrator under different experimental conditions. The radiant power was characterized using laser powermeter. The degree of conversion (DC) achieved on the top and bottom of the bulk fill composite resin was assessed using FTIR. The occlusal face of forty human molars were flattened until left 2.0mm of remaining dentin. Restorations were built up using self-etching adhesive system (ClearFil SE Bond, Kuraray) and bulk fill composite resin, a flowable (SDR, Dentsply) or regular viscosity (AURA, SDI). The pulp chamber temperature was measured using J-type thermocouple with or without pulpal microcirculation simulation. The maximum temperature rise during the light activation of the adhesive system and composite resin were recorded. Data were analyzed using t-Student test, two-way and three-way ANOVA, all analyses considered α= 0.05. The irradiance and radiant power emitted by LCUs was without any material interposed to top sensor and lowest when through the 3.0 mm of composite resin over 2.0mm of dentin. In general, Bluephase G2 had higher irradiance and radiant power than VALO Cordless. Composite resin, LCU, and the region affected the DC. Pulpal microcirculation simulation significantly the temperature rise. The highest temperature was found for light activation of by adhesive system. VALO Cordless resulted on lower temperature change during activation of adhesive system only in absence of pulpal microcirculation simulation. Therefore, pulpal microcirculation simulation can dissipated the heat, resulting in lower temperature changes. SDR allows more light transmission and achieved higher DC than AURA. The temperature rise was lower for light activation of bulk fill composite resins than when adhesive systems was used. The clinical relevance is the use pulpal microcirculation simulation is important in heat generation by light curing units and bulk fill resins, while the critical point in the increase in temperature is related to the light activation of adhesive system.